A method for preparing a supported beta molecular sieve / glass microbead composite catalyst
Through the method of dynamic crystallization in stainless steel microchannels, the supported β molecular sieve/glass microbead composite catalyst is quickly prepared, which solves the problems of long growth cycle, high time cost and poor batch stability in the production process of β molecular sieve catalyst, and The immobilization treatment reduces the cost of catalyst separation and recovery and achieves more efficient catalytic performance.
Patent Information
- Application Number
- CN202310910800.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-24
AI Technical Summary
The existing β-molecular sieve catalysts have problems such as long growth cycle, high time cost and poor batch stability during the production process, and the catalyst separation and recycling are difficult, resulting in high separation costs.
The method of dynamic crystallization in the stainless steel microcontroller is used to quickly prepare the load -type β molecular sieve/glass microfin composite catalyst to reduce the difficulty of separation and recycling of the catalyst by fixed treatment.
It shortens the growth cycle of beta molecular sieves, improves particle uniformity and batch stability, reduces catalyst separation and recovery costs, and provides more efficient catalytic performance.
Smart Images

Figure CN117019213B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a method for preparing a loaded beta molecular sieve / glass microbead composite catalyst that can be quickly and evenly grown in a microchannel. Background Art
[0002] β molecular sieve was first synthesized by Wadlinger of Mobil Oil Company in the United States in 1967 using the classic hydrothermal crystallization method (USP3308069). Its subsequent research patents (EP0159846, EP0159847) further reported the excellent catalytic performance of β molecular sieve, disclosing that β molecular sieve has excellent activity for hydrocarbon cracking and isomerization. β molecular sieve has a complex structure, a crystal particle size of ≤0.5μm, a high silicon-aluminum ratio and better thermal and acid stability. Therefore, it exhibits good thermal stability, acid resistance, coking resistance and catalytic activity in many catalytic reactions. It is widely used in many catalytic reactions in oil refining and petrochemical processes such as hydrogenation, cracking, isomerization, alkylation, olefin hydration, dewaxing and photocatalysis. Since β molecular sieve is the only high-silicon zeolite in the world with a three-dimensional twelve-membered ring pore system, its pore size is similar to that of Y molecular sieve and its pore structure is superior to that of ZMS-5 molecular sieve. It integrates the advantages of Y and ZSM-5 in one, and its silicon-aluminum ratio can be adjusted within a very large range, so that its acid performance and stability can be controlled to a certain extent, which provides a prerequisite for its application in functional catalytic cracking catalysts.
[0003] The common method for synthesizing β molecular sieve is to prepare a mixture of silicon source, aluminum source, sodium source, template and water into a slurry, and then hydrothermally crystallize it at 75-200°C in an autoclave for 3-60 days. However, this method has the problem of low production efficiency due to the large volume of the entire reaction solution and the long crystallization time, which is not conducive to large-scale industrial production. And the β molecular sieve nanoparticles obtained by this method have the following two severe challenges: First, due to the high surface energy of the nanoparticles, the nanoparticles are very easy to agglomerate into micron-sized particles during actual use, resulting in a decrease in catalytic activity; secondly, the separation and recovery of β molecular sieve nanoparticles after the reaction is difficult. At present, the nanoparticles are mainly separated from the reaction system by membrane filtration, but after several uses, the membrane pores are easily blocked, resulting in the separation membrane being unusable as a whole. The replacement cost of the membrane accounts for a large proportion of the entire process cost.
[0004] In order to solve the above problems, researchers have proposed two solutions: first, β molecular sieve nanoparticles are granulated and formed. Patent CN1704163A introduces a balancer and a binder into the β molecular sieve spray forming process, and obtains a β molecular sieve microsphere catalyst after ion exchange, drying and calcination. On the one hand, the catalytic activity of the β molecular sieve is improved, and on the other hand, the mechanical strength of the microsphere β molecular sieve is guaranteed. However, this method will lead to low utilization of the catalyst inside the microsphere, and only the β molecular sieve on the surface of the microsphere can participate in the catalytic oxidation reaction. Problems; Second, β nanoparticles are loaded on a carrier to make a loaded β molecular sieve. Patent CN102530982A uses an in-situ hydrothermal method with cordierite as the carrier and crystallizes at 120°C for 4 days to obtain a layer of β molecular sieve membrane grown on a cordierite honeycomb ceramic carrier. However, the carrier used in this method is not easy to modify, and the carrier pretreatment requires the use of a large amount of acid solution, which is not conducive to green environmental protection. Patent CN1596150A prepares a composite β molecular sieve catalyst by loading the β molecular sieve on a porous inorganic oxide carrier after aging the mother liquor at room temperature for 48 hours and then crystallizing at 180°C for 4 hours. The composite β molecular sieve catalyst exhibits good catalytic performance in the alkylation reaction of benzene and ethylene to produce styrene and is easily separated from the liquid phase. However, the carrier used in this method has a small specific surface area and is not easy to modify, and the synthesis method is time-consuming.
[0005] In our previous work Chemical Engineering Journal 235(2014)75-82, titanium silicon molecular sieve nanoparticles were successfully loaded onto glass microsphere carriers to prepare composite catalysts after crystallization in a hydrothermal crystallization reactor for 48 hours using glass microspheres as carriers. The molecular sieve catalyst obtained by this method is coated on the outer surface of the carrier, thus completely solving the waste of internal catalyst caused by granulation molding; and glass microspheres as carriers have obvious advantages such as large specific surface area, easy surface modification, high thermal stability and chemical stability, low cost, reusability, and green environmental protection. However, this method is currently carried out in a stainless steel hydrothermal crystallization reactor, and it still faces the problems of long crystallization time and low production efficiency. Therefore, it is necessary to study and develop a method for quickly and uniformly synthesizing a loaded molecular sieve / glass microsphere composite catalyst. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a preparation method of a supported β molecular sieve / glass microbead composite catalyst in view of the problems existing in the current β molecular sieve catalyst. The preparation method can quickly prepare a supported β molecular sieve / glass microbead composite catalyst in a confined space, and has the characteristics of a short growth cycle of the β molecular sieve, low synthesis time cost, and more uniform β molecular sieve particles. Moreover, the difficulty of subsequent catalyst separation and recovery can be effectively reduced through immobilization treatment, and the separation cost can be reduced.
[0007] To this end, the present invention provides a method for preparing a supported β molecular sieve / glass microbead composite catalyst, which prepares the supported β molecular sieve / glass microbead composite catalyst in a stainless steel microchannel, comprising:
[0008] Step A, stirring and mixing a silicon source, an aluminum source, a template, a sodium source and water to obtain a β molecular sieve mother solution;
[0009] Step B, adding the β molecular sieve mother liquid and the pretreated glass microbead carrier into a stainless steel microchannel, sealing the microchannel and fixing it in a homogeneous reactor, and dynamically crystallizing to obtain a crystallized solid-liquid mixture;
[0010] Step C, separating the solid-liquid mixture to recover the solid, washing it multiple times and then drying it to obtain a dry Na-supported β molecular sieve / glass microbead composite catalyst precursor;
[0011] Step D, in a water bath environment, dispersing the Na-supported β molecular sieve / glass microbead composite catalyst precursor in an ammonium chloride aqueous solution, performing an ion exchange reaction for 4 to 6 hours, repeating the reaction 2 to 6 times, and then collecting the product and drying it to obtain a dried H-supported β molecular sieve / glass microbead composite catalyst precursor;
[0012] Step E: calcining the dried H-supported β molecular sieve / glass microbead composite catalyst precursor to remove the template agent, thereby obtaining a supported β molecular sieve / glass microbead composite catalyst.
[0013] According to the present invention, in step A, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the sodium source is calculated as Na2O, and the mixing molar ratio is: silicon source / aluminum source = 10-100, template / silicon source = 0.01-0.4, sodium source / silicon source = 0.01-0.12, water / silicon source = 2.0-30.0.
[0014] In the present invention, the silicon source is tetraethyl orthosilicate, white carbon black, silica sol or macroporous silica gel.
[0015] In the present invention, the aluminum source is sodium aluminate, hydrated aluminum oxide or aluminum sulfate.
[0016] In the present invention, the template agent is tetraethylammonium hydroxide, tetrapropylammonium hydroxide or tetraethylammonium bromide.
[0017] Preferably, the sodium source is sodium hydroxide.
[0018] According to the present invention, in step D, the concentration of the aqueous ammonium chloride solution is 1 mol / L; preferably, the amount of the aqueous ammonium chloride solution is 100 mL per gram of Na-supported β molecular sieve / glass microbead composite catalyst precursor.
[0019] In some embodiments of the present invention, in step B, the temperature of the dynamic crystallization is 100-170° C., and the time of the dynamic crystallization is 5-48 hours.
[0020] In some embodiments of the present invention, in step C, the drying temperature is 80-120°C.
[0021] In some embodiments of the present invention, in step D, the temperature of the water bath environment is 60-100° C. In some embodiments of the present invention, in step D, the drying temperature is 80-120° C.
[0022] In some embodiments of the present invention, in step D, the calcination temperature is 550-600° C., and the calcination time is 5-8 hours.
[0023] In the present invention, the stainless steel microchannel is made of 304 or 316 stainless steel; the inner diameter of the stainless steel microchannel is 4 mm, and the outer diameter is 2 to 14 mm.
[0024] In some embodiments of the present invention, the mass ratio of the glass microbead carrier to the β molecular sieve mother liquor is 0.1 to 3.0.
[0025] According to the present invention, the glass microsphere carrier is a pretreated glass microsphere carrier.
[0026] In some embodiments of the present invention, the preparation method of the pretreated glass microsphere carrier includes: treating the glass microspheres with water in a subcritical state at 300°C for 0.1 to 3 hours, then acid washing and water washing, and then calcining at 100-600°C for 2-6 hours to obtain the pretreated glass microsphere carrier.
[0027] The present invention also provides a supported beta molecular sieve / glass microbead composite catalyst prepared by the above-mentioned preparation method of the present invention.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The preparation method of the supported β molecular sieve / glass microbead composite catalyst provided by the present invention can quickly prepare the supported β molecular sieve / glass microbead composite catalyst in a microchannel, greatly shorten the growth cycle of the β molecular sieve compared with the traditional stainless steel self-pressing crystallization reactor, and the β molecular sieve particles of different batches are uniform and controllable. The preparation process can solve the problems of long growth cycle, high time cost and poor batch stability in the production process of β molecular sieve. At the same time, by immobilizing the β molecular sieve, the difficulty of catalyst recovery can be effectively reduced, the separation cost can be reduced, and a new research idea can be provided for the industrial application of β molecular sieve. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to make the present invention easy to understand, the present invention will be described in detail below with reference to the accompanying drawings.
[0031] Figure 1 is a SEM image of the glass microsphere carrier in Example 1;
[0032] Figure 2 This is a SEM image of the supported β molecular sieve / glass microbead composite catalyst prepared in the microchannel in Example 1;
[0033] Figure 3 This is a SEM image of the supported β molecular sieve / glass microbead composite catalyst prepared in the microchannel in Example 2;
[0034] Figure 4 This is a SEM image of the supported β molecular sieve / glass microbead composite catalyst prepared in the microchannel in Example 3;
[0035] Figure 5 This is a SEM image of the supported β molecular sieve / glass microbead composite catalyst prepared in the microchannel in Example 4;
[0036] Figure 6 This is a SEM image of the supported β molecular sieve / glass microbead composite catalyst prepared in the microchannel in Example 5.
[0037] Figure 7 This is a SEM image of the supported β molecular sieve / glass microbead composite catalyst prepared in the crystallization reactor in Comparative Example 1. DETAILED DESCRIPTION
[0038] To make the present invention easy to understand, the present invention will be described in detail below. However, before describing the present invention in detail, it should be understood that the present invention is not limited to the specific embodiments described. It should also be understood that the terms used herein are only for describing specific embodiments and are not intended to be limiting.
[0039] Where a numerical range is provided, it is understood that each intervening value between the upper and lower limits of the range and any other specified or intervening values in the specified range is encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges and are also encompassed within the present invention, subject to any explicitly excluded limits in the specified ranges. Where a specified range includes one or two limits, ranges excluding either or both of those included limits are also encompassed within the present invention.
[0040] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described.
[0041] I. Terminology
[0042] The term "water" as used in the present invention refers to deionized water, distilled water, pure water or ultrapure water.
[0043] The term "water in a subcritical state" as used in the present invention refers to water heated to a temperature above the boiling point and below the critical point, and the system pressure is controlled to keep the water in a liquid state.
[0044] The term "PX" used in the present invention is the English abbreviation of the catalytic reaction product, p-xylene.
[0045] The term "Na-supported β molecular sieve / glass microbead composite catalyst precursor" in the present invention refers to a Na-supported β molecular sieve / glass microbead composite catalyst that has not been calcined to remove the template, and its β molecular sieve pores are not released and do not have a shape-selective catalytic effect.
[0046] The term "H-loaded β molecular sieve / glass microbead composite catalyst precursor" in the present invention refers to an H-loaded β molecular sieve / glass microbead composite catalyst that has not been calcined to remove the template, deammoniate, or remove water, and whose β molecular sieve pores are not released and does not have a shape-selective catalytic effect.
[0047] II. Implementation Plan
[0048] As mentioned above, the existing method for preparing loaded molecular sieve / glass microbead composite catalyst in a hydrothermal crystallization reactor has the problems of long crystallization time, low production efficiency and poor batch stability. In view of this, the present invention has conducted extensive research on the preparation technology of loaded β molecular sieve / glass microbead composite catalyst.
[0049] After research, the inventor innovatively designed and proposed the idea of preparing loaded β molecular sieves in a confined space with glass microbeads as carriers based on the high-efficiency heat transfer characteristics in the confined space of the microreactor. This idea has the following advantages: (1) Using microchannels instead of hydrothermal crystallization kettles to grow loaded β molecular sieves, since stainless steel micro-pipes have a large specific surface area, they have excellent heat transfer performance, and the increase in the heating rate can shorten the induction cycle and accelerate the molecular sieve nucleation process, thereby reducing the long-cycle growth time at high temperature, so that the molecular sieve particle size loaded on the carrier is reduced; (2) The homogeneous nucleation of the β molecular sieve mother liquor is reduced, the utilization rate of the raw materials is greatly improved, and the wastewater discharged during the production process is greatly reduced; (3) The temperature and concentration gradients in the microchannel are very narrow, the crystallization environment is relatively uniform, the growth process has a strong consistency, and the synthesized molecular sieve particles have high batch stability and good catalytic performance; (4) Immobilization of the molecular sieve catalyst can reduce the difficulty of the separation process, facilitate the recovery of the catalyst, and reduce the cost of separation and extraction.
[0050] To achieve the aforementioned object of the invention, the technical solution adopted by the present invention comprises the following steps:
[0051] (1) Pretreatment of glass microsphere carrier: 5 g of 50-200 μm glass microspheres and 200 g of deionized water were placed in an autoclave reactor. The autoclave reactor was sealed and heated to 300° C. The subcritical state was maintained for 0.1-3 h and then the heating power was turned off. After the reactor temperature dropped to room temperature, the etched glass microspheres were taken out, washed with deionized water until neutral, and then shaken with 0.5-1.0 M hydrochloric acid solution in a 50° C. water bath for 5-10 h, and then washed with deionized water until neutral. After drying, the pretreated glass microsphere carrier was calcined in a muffle furnace at 100-600° C. for 2-6 h to obtain a pretreated glass microsphere carrier for use;
[0052] (2) Synthesis of β molecular sieve mother liquor: Add a silicon source to a vigorously stirred mixed solution of water and template aqueous solution at room temperature, stir until the solution is clear, add an aluminum source, stir until the aluminum source is dissolved, then add a sodium source, and continue stirring for 2 to 6 hours to obtain a β molecular sieve mother liquor;
[0053] (3) placing the pretreated glass microbeads obtained in step (1) and the β molecular sieve mother liquor obtained in step (2) into a stainless steel microchannel, sealing the microchannel and fixing it in a homogeneous reactor, and performing dynamic crystallization at 100 to 170° C. for 5 to 48 hours to obtain a crystallized solid-liquid mixture;
[0054] (4) separating the solid-liquid mixture to recover the solid, washing it multiple times and drying it at 80-120° C. to obtain a dry Na-supported β molecular sieve / glass microbead composite catalyst precursor;
[0055] (5) dispersing the obtained Na-supported β molecular sieve / glass microbead composite catalyst precursor in an aqueous ammonium chloride solution in a water bath environment at 60 to 100° C., performing an ion exchange reaction for 4 to 6 hours, repeating the reaction 2 to 6 times, and then collecting the product and drying it at 80 to 120° C. to obtain an untreated H-supported β molecular sieve / glass microbead composite catalyst precursor;
[0056] (6) The dried untreated H-supported β molecular sieve / glass microbead composite catalyst precursor is calcined at 550-600° C. for 5-8 hours to remove the template agent, thereby obtaining a supported β molecular sieve / glass microbead composite catalyst.
[0057] In the above step (1), the glass microsphere carrier is treated with water at a subcritical state of 300° C. for 0.5 to 3 hours before use. The specific method is referred to the previous work of this research group: Chemical Engineering Journal 235 (2014) 75-82.
[0058] In the above step (2), the silicon source is tetraethyl orthosilicate, white carbon black, silica sol or macroporous silica gel; the aluminum source is sodium aluminate, hydrated alumina or aluminum sulfate; the template is tetraethylammonium hydroxide, tetrapropylammonium hydroxide or tetraethylammonium bromide; and the sodium source is sodium hydroxide.
[0059] The chemical composition (molar ratio) of the synthetic β molecular sieve mother liquor is: based on 1 mole of silicon source (calculated as SiO2), the aluminum source (calculated as Al2O3) is 0.01-0.1, the template is 0.01-0.4, the sodium source (calculated as Na2O) is 0.01-0.12, and water is 2.0-30.0.
[0060] In the present invention, the template is added in the form of an aqueous solution, wherein the tetrapropylammonium hydroxide aqueous solution is a finished product with a mass fraction of 25% and is sold on the market.
[0061] It should be understood by those skilled in the art that in the above chemical composition (molar ratio), the "water" is the added water, which does not include the water contained in the template aqueous solution.
[0062] The method for rapidly preparing a loaded beta molecular sieve / glass microbead composite catalyst in a microchannel provided by the present invention uses the microchannel as a hydrothermal crystallization device, and the crystallization time is shortened to 5 to 48 hours.
[0063] Generally, during the preparation of supported molecular sieve catalysts, a static crystallization method is usually used to prepare and obtain a crystallized milky white solid-liquid mixture. However, the inventors have found that in the preparation of supported β molecular sieve / glass microbead composite catalysts, a dynamic crystallization method is used, especially in the above step (3), wherein the dynamic crystallization refers to fixing the microchannel reactor in a homogeneous reactor and setting the rotation speed within the range of 4 to 15 rpm for rotational crystallization, which can make the mother liquid contact with the carrier more fully and make the molecular sieve grow more evenly on the carrier surface.
[0064] The present invention has no particular limitation on the number of washing times in the "multiple washings" in the above step (4), as long as the washing is performed until the solution is clear.
[0065] In the above step (5), the concentration of the aqueous ammonium chloride solution is 1 mol / L; preferably, the amount of the aqueous ammonium chloride solution is 100 mL per gram of Na-supported β molecular sieve / glass microbead composite catalyst precursor.
[0066] The β molecular sieve supported on the glass microbead carrier synthesized in the above step (6) is in the form of spherical crystals.
[0067] The microchannels used in the present invention are liquid chromatography columns with different diameters, and both ends of the columns can be sealed with nuts.
[0068] The stainless steel microchannel is made of 304 or 316 stainless steel; the inner diameter of the stainless steel microchannel is 4 mm, and the outer diameter is 2-14 mm.
[0069] The present invention aims at the problems existing in the current β molecular sieve catalyst and provides a method for quickly preparing a loaded β molecular sieve / glass microbead composite catalyst in a confined space. At present, the research on β molecular sieves at home and abroad mainly focuses on the preparation of nanoparticle β molecular sieves, while the research on loaded β molecular sieves is still relatively small. Therefore, based on the existing loaded TS-1 molecular sieve / glass microbead composite catalyst, this research group innovatively proposed for the first time to use glass microbeads as carriers to quickly and uniformly synthesize loaded β molecular sieves in microchannels and explore their performance. Finally, the loaded β molecular sieve / glass microbead composite catalyst was successfully obtained. The synthesis method has the characteristics of short growth cycle of β molecular sieve, low synthesis time cost and more uniform β molecular sieve particles. The difficulty of subsequent catalyst separation and recovery can be effectively reduced through immobilization treatment, and the separation cost can be reduced.
[0070] III. Examples
[0071] In order to make the present invention easier to understand, the present invention will be further described in detail below in conjunction with examples, which are merely illustrative and are not intended to limit the scope of application of the present invention. The raw materials or components used in the present invention can be obtained through commercial channels or conventional methods unless otherwise specified.
[0072] In the following examples and comparative examples, all reagents used were commercially available chemically pure reagents.
[0073] In the present invention, the components of the reaction liquid are quantitatively detected by gas chromatography, which is carried out on a Shimadzu 2010 gas chromatograph equipped with a DB-WAX (30m×0.320mm, film thickness 0.25μm) capillary column and an FID detector. The conversion rate of 2,5-dimethylfuran is calculated by the internal standard method according to formula (I); the selectivity of PX is calculated by the internal standard method according to formula (II). The selectivity of PX is calculated by the internal standard method according to formula (III). In the present invention, based on the total mass of the reaction solution, the total weight ratio of the internal standard to the reactant solution is (0.01-0.3):1, preferably the total weight ratio of the internal standard to the reactant solution is (0.01-0.1):1, and further preferably the total weight ratio of the internal standard to the reactant solution is 0.02. There is no particular limitation on the internal standard in the present invention, and the preferred internal standard is n-decane.
[0074]
[0075] In formula (I):
[0076] n0 is the amount of the initial substance of 2,5-dimethylfuran added, in mol;
[0077] n1 is the amount of 2,5-dimethylfuran remaining after the reaction is completed, which is detected using an internal standard and is expressed in mol.
[0078]
[0079] In formula (II):
[0080] n0 is the amount of the initial substance of 2,5-dimethylfuran added, in mol;
[0081] n1 is the amount of 2,5-dimethylfuran remaining after the reaction is completed, which is detected using an internal standard and is expressed in mol.
[0082] n PX It is the amount of PX generated after the reaction is completed, detected using an internal standard, and the unit is mol.
[0083]
[0084] In formula (III):
[0085] n0 is the amount of the initial substance of 2,5-dimethylfuran added, in mol;
[0086] n PX It is the amount of PX substance generated after the reaction is completed, detected by internal standard, and the unit is mol.
[0087] Embodiment 1:
[0088] (1) Add 5 g of glass beads and 200 g of deionized water to a 250 mL autoclave reactor, seal the autoclave reactor and gradually heat it to 300°C. After maintaining the subcritical state for 2 hours, turn off the heating power supply. After the reactor cools to room temperature, open the reactor and take out the etched glass beads. Wash the glass beads with deionized water several times until neutral, and then dry them in an oven at 80°C for use.
[0089] (2) Take 2.5 g of the etched and dried glass beads in a 250 mL conical flask, add 200 mL of 0.5 M hydrochloric acid solution, and oscillate in a constant temperature oscillator for 6 h at 200 r / min and 50°C. After acid washing, wash with deionized water several times until neutral, and then place in an oven at 80°C to dry for use.
[0090] (3) Take 5 g of the acid-washed and dried glass beads, wash them with running deionized water at 80°C for 5 to 8 h at a flow rate of 5 mL / min, and dry them in an oven at 80°C for later use.
[0091] (4) 3 g of washed and dried glass microspheres were calcined in a muffle furnace at 600° C. for 4 h to obtain the glass microsphere carrier to be loaded.
[0092] (5) In a 100 mL beaker, add 4.4 g of deionized water and 10.095 g of tetraethylammonium hydroxide solution, add 3.6 g of white carbon black under vigorous stirring, stir until the silicon source is dissolved, then add 0.23 g of sodium aluminate and 0.12 g of sodium hydroxide, and continue stirring at room temperature for 6 h to obtain the β molecular sieve mother liquor.
[0093] (6) Take 1.0 g of the glass microsphere carrier calcined in step (4), add it into a stainless steel microchannel with an inner diameter of 6 mm, then add 4.0 g of the β molecular sieve mother liquor prepared in step (5), seal the microchannel and place it in a 150° C. homogeneous reactor for dynamic crystallization for 18 h, then take out the Na-loaded β molecular sieve / glass microsphere composite catalyst precursor.
[0094] (7) In a 70° C. water bath, 1 g of the obtained Na-loaded β-molecular sieve / glass microbead composite catalyst precursor was dispersed in 100 mL of a 1 mol / L aqueous solution of ammonium chloride, and an ion exchange reaction was performed for 4 hours. The reaction was repeated 3 times, and then the product was collected and dried at 100° C. to obtain an untreated H-loaded β-molecular sieve / glass microbead composite catalyst precursor.
[0095] (8) Finally, the H-loaded β-molecular sieve / glass microbead composite catalyst precursor was calcined in a muffle furnace at 550° C. for 6 h to remove the template agent, thereby obtaining a loaded β-molecular sieve / glass microbead composite catalyst.
[0096] The supported β molecular sieve / glass microbead composite catalyst was analyzed by scanning electron microscope using SU1510 scanning electron microscope (Hitachi High-Tech Naka Corporation, Japan). Figure 2 As shown, the scanning electron microscope image of the loaded composite catalyst shows that the spherical granular β molecular sieve has been uniformly grown on the surface of the glass microbead carrier.
[0097] (9) The catalyst performance test was carried out in a high-temperature and high-pressure reactor. 0.6 g of a supported β molecular sieve / glass microbead composite catalyst, 10.0 g of 2,5-dimethylfuran, 85 mL of n-heptane, 5.0 g of an internal standard substance, n-decane, were added to a 160 mL reactor, 2.0 MPa of ethylene was added, and the reaction was heated to 250°C for 24 hours to obtain PX. According to the test and calculation of formula (I), (II) and (III), the conversion rate of 2,5-dimethylfuran was >99%, the selectivity of PX was 90%, and the yield was 90%.
[0098] Embodiment 2:
[0099] This embodiment is different from Embodiment 1 in that:
[0100] In step (6), 1.0 g of the calcined carrier and 6.0 g of β molecular sieve mother liquor were added, and the molecular sieve growth cycle was 18 h.
[0101] The remaining reaction conditions were the same as those in Example 1. After 24 hours of reaction, the conversion rate of 2,5-dimethylfuran was >99%, the PX selectivity was 90%, and the yield was 90%. Figure 3 shown.
[0102] Embodiment 3:
[0103] This embodiment is different from Embodiment 1 in that:
[0104] In step (6), 1.0 g of the calcined carrier and 4.0 g of β molecular sieve mother liquor were added, and the molecular sieve growth cycle was 24 h.
[0105] The remaining reaction conditions were the same as those in Example 1. After 24 hours of reaction, the conversion rate of 2,5-dimethylfuran was >99%, the PX selectivity was 90%, and the yield was 90%. Figure 4 shown.
[0106] Embodiment 4:
[0107] This embodiment is different from Embodiment 1 in that:
[0108] In step (6), a microchannel with an inner diameter of 8 mm is used, and the molecular sieve growth cycle is 18 h.
[0109] The remaining reaction conditions were the same as those in Example 1. After 24 hours of reaction, the conversion rate of 2,5-dimethylfuran was >99%, the PX selectivity was 90%, and the yield was 90%. Figure 5 shown.
[0110] Embodiment 5:
[0111] This embodiment is different from Embodiment 1 in that:
[0112] In step (4), the carrier is calcined at 300° C. for 4 h, and then used in step (6) to be loaded into the microchannel with the β molecular sieve mother liquid for dynamic crystallization. The molecular sieve growth cycle is 18 h.
[0113] The remaining reaction conditions were the same as those in Example 1. After 24 hours of reaction, the conversion rate of 2,5-dimethylfuran was >99%, the PX selectivity was 90%, and the yield was 90%. Figure 6 shown.
[0114] Comparative Example 1:
[0115] The difference between this comparative example and Example 1 is that:
[0116] In step (6), a hydrothermal crystallization kettle with a 50 mL polytetrafluoroethylene liner was used, 4.0 g of the carrier calcined in step (4) and 16 g of the β molecular sieve mother liquor prepared in step (5) were added, and the crystallization kettle was placed in a 150° C. homogeneous reactor for crystallization for 84 h. The remaining post-treatment conditions were the same as those in Example 1. After 24 h of reaction, the conversion rate of 2,5-dimethylfuran was >80%, the PX selectivity was 30%, and the yield was 24%. The scanning electron microscope photo is shown in FIG. Figure 7 shown.
[0117] It can be seen from the scanning electron microscope images of the above examples that the β molecular sieves loaded in different batches can be evenly distributed on the surface of the carrier, and the synthetic batches of the loaded β molecular sieves have high stability.
[0118] It should be noted that the preferred embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a supported β molecular sieve / glass microbead composite catalyst, which prepares a supported β molecular sieve / glass microbead composite catalyst in a stainless steel microchannel, comprising: Step A, stirring and mixing a silicon source, an aluminum source, a template, a sodium source and water to obtain a β molecular sieve mother solution; Step B, adding the β molecular sieve mother liquid and the pretreated glass microbead carrier into a stainless steel microchannel, sealing the microchannel and fixing it in a homogeneous reactor, and dynamically crystallizing to obtain a crystallized solid-liquid mixture; Step C, separating the solid-liquid mixture to recover the solid, washing it multiple times and then drying it to obtain a dry Na-supported β molecular sieve / glass microbead composite catalyst precursor; Step D, in a water bath environment, dispersing the Na-loaded β molecular sieve / glass microbead composite catalyst precursor in an aqueous solution of ammonium chloride, performing an ion exchange reaction for 4 to 6 hours, repeating the reaction 2 to 6 times, and then collecting the product and drying it to obtain a dried H-loaded β molecular sieve / glass microbead composite catalyst precursor; Step E, calcining the dried H-supported β molecular sieve / glass microbead composite catalyst precursor to remove the template agent to obtain a supported β molecular sieve / glass microbead composite catalyst; In step B, the temperature of the dynamic crystallization is 100-170° C., and the time of the dynamic crystallization is 5-48 h; The dynamic crystallization refers to fixing the microchannel reactor in the homogeneous reactor and setting the rotation speed in the range of 4 to 15 rpm for rotational crystallization; The preparation method of the pretreated glass microsphere carrier comprises: treating the glass microsphere with water at a subcritical state of 300° C. for 0.1 to 3 hours, then acid washing and water washing, and then calcining at 100-600° C. for 2-6 hours to obtain the pretreated glass microsphere carrier.
2. The preparation method according to claim 1, characterized in that: In step A, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the sodium source is calculated as Na2O, and the mixing molar ratio is: silicon source / aluminum source = 10-100, template / silicon source = 0.01-0.4, sodium source / silicon source = 0.01-0.12, and water / silicon source = 2.0-30.
0.
3. The preparation method according to claim 2, characterized in that: The silicon source is tetraethyl orthosilicate, white carbon black, silica sol or macroporous silica gel; And / or, the aluminum source is sodium aluminate, hydrated aluminum oxide or aluminum sulfate; And / or, the template is tetraethylammonium hydroxide, tetrapropylammonium hydroxide or tetraethylammonium bromide; And / or, the sodium source is sodium hydroxide.
4. The preparation method according to claim 1, characterized in that In step D, the concentration of the aqueous ammonium chloride solution is 1 mol / L; the amount of the aqueous ammonium chloride solution used is 100 mL per gram of the sodium-supported β molecular sieve / glass microbead composite catalyst precursor.
5. The preparation method according to claim 1, characterized in that: In step C, the drying temperature is 80-120°C.
6. The preparation method according to claim 1, characterized in that In step D, the temperature of the water bath environment is 60-100° C.; and / or, the drying temperature is 80-120° C.; and / or, the calcination temperature is 550-600° C., and the calcination time is 5-8 h.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The stainless steel microchannel is made of 304 or 316 stainless steel; the inner diameter of the stainless steel microchannel is 4 mm and the outer diameter is 2-14 mm.
8. The preparation method according to any one of claims 1 to 6, characterized in that: The mass ratio of the glass microbead carrier to the beta molecular sieve mother liquor is 0.1-3.
0.
9. The preparation method according to claim 7, characterized in that: The mass ratio of the glass microbead carrier to the beta molecular sieve mother liquor is 0.1-3.
0.
10. A supported β molecular sieve / glass microbead composite catalyst prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing titanium silicalite film by dynamic in-situ hydrothermal method
CN102530982A
Catalyst containing microporous molecular sieve in mesoporous support and method for making same
CN1596150A
Molecular screen microspherical catalyst
CN1704163A
Preparation of zeolite beta
EP0159846A2
Preparation of zeolite beta
EP0159847A2